Local Fractional Operator for a One-Dimensional Coupled Burger Equation of Non-Integer Time Order Parameter - Sunday O. Edeki; Grace O. Akinlabi (Journal of Mathematical and Fundamental Sciences, 2018)
In this study, approximate solutions of a system of time-fractional coupled Burger equations were obtained by means of a local fractional operator (LFO) in the sense of the Caputo derivative. The LFO technique was built on the basis of the standard differential transform method (DTM). Illustrative examples used in demonstrating the effectiveness and robustness of the proposed method show that the solution method is very efficient and reliable as "“ unlike the variational iteration method "“ it does not depend on any process of identifying Lagrange multipliers, even while still maintaining accuracy.